PENGARUH DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA DIMEDIASI KEPUASAN KERJA (Studi Pada Guru SMA Negeri Di Kabupaten Jepara) - Slamet Riyadi, 11.52.02.0020 (Students Journal of Economic and Management, 2013)
The research objective was to examine the effect of labor discipline and motivation to work on teacher performance and job satisfaction as the mediation, studies on teacher high schools in the district of Jepara. Samples used in these researches as much as 191 people with the sampling technique is proportional random sampling gives equal opportunities are limitless for each element of the population to be selected into the sample taken by a proportional amount. Analysis using multiple linear regression test. The research results can be summarized as follows: Discipline of work has no effect on job satisfaction. Work motivation positive and significant effect on job satisfaction, work discipline and significant positive effect on performance, motive does not affect the performance of work, job satisfaction has a positive effect on performance, job satisfaction as a mediating variable is not able to explain the effect on the performance of work discipline and work motivation. Keyword: Discipline of work, work motivation, job satisfaction and performance